2012
DOI: 10.1136/gutjnl-2012-302029
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-mesenchymal stem cells are a major source of interleukin-7 and sustain colitis by forming the niche for colitogenic CD4 memory T cells

Abstract: ObjectiveInterleukin (IL)-7 is mainly produced in bone marrow (BM) that forms the niche for B cells. We previously demonstrated that BM also retains pathogenic memory CD4 T cells in murine models of inflammatory bowel disease (IBD). However, it remains unknown whether BM-derived IL-7 is sufficient for the development of IBD and which cells form the niche for colitogenic memory CD4 T cells in BM.DesignTo address these questions, we developed mice in which IL-7 expression was specific for BM, and identified coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 25 publications
4
41
0
Order By: Relevance
“…2A). Second, IL-7 is a critical cytokine for effector/memory T cell survival, IL-7 levels produced by bone marrow stromal cells increase in bone loss-associated diseases like RA (11,27,28), and IL-7 has been involved with survival of memory CD4 + T cells in the bone marrow niche in colitis (42). Thus, a2b1 can provide an additional help for maintaining the survival of Th17 cells in the bone marrow of IL-7-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Second, IL-7 is a critical cytokine for effector/memory T cell survival, IL-7 levels produced by bone marrow stromal cells increase in bone loss-associated diseases like RA (11,27,28), and IL-7 has been involved with survival of memory CD4 + T cells in the bone marrow niche in colitis (42). Thus, a2b1 can provide an additional help for maintaining the survival of Th17 cells in the bone marrow of IL-7-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of focusing on the potential immunosuppressive and anti-inflammatory actions of BM-MSCs in animal models of IBD as reported in recent studies [30,31], the present study tracked the homing and differentiation of transplanted BM-MSCs in the injured intestines. In IDMtreated rats, transplanted PKH26-labelled cells resided in the injured intestinal areas, mainly in the crypts and villi.…”
Section: Discussionmentioning
confidence: 90%
“…In this regard, Duijvestein et al [44] have shown that in vitro MSCs activation by INFγ increases the immunosuppressive capacity of cells and their in vivo therapeutic efficacy in mice with colitis induced by trinitrobenzene sulfonate. On the other hand, Nemoto et al [47], in a murine model, have shown that bone marrow MSCs constitute the main source of IL-7 production, and may play an etiopathogenic role in IBD by forming a niche for colitogenic CD4+ memory T cells in bone marrow.…”
Section: Page 4 Of 25mentioning
confidence: 97%